Shopping for Health: Vitamin D - Lauren Foster; Wendy J. Dahl (EDIS)
Vitamin D needs can be met by eating foods containing Vitamin D and taking vitamin supplements, but few foods are consistent in their levels of vitamin D. This 6-page fact sheet will help you be an informed shopper and find brands that meet your vitamin D needs. Written by Lauren Foster and Wendy J. Dahl and published by the UF Department of Food Science and Human Nutrition, May 2011.